Analisa Daya Saing Usaha Anyaman Keranjang di Kabupaten Simalungun dengan menggunakan Model Diamond Porter - Saragih, Liharman; Saragih, Arno Frayliado; Purba, Rizky Fadhila; Sakti, Bima Perdana; ., Nurhasanah; Yopandi, Trizki (Jurnal Ecogen, 2024)
This study aims to analyze the competitive advantage by using the Porter Diamond Model in the basket weaving craft business in Nagori Sirpang Dalig Raya, Kecataman Pematang Raya, Simalungun Regency. The research method used is descriptive with a qualitative approach. Data collection techniques were carried out by interview, observation and documentation. The results showed important determinants in the competitive advantage of woven basket craftsmen in accordance with porter's diamond model, consisting of factor conditions; demand conditions; company structure, strategy and competition; related industries and supporting industries; and the role of government. The formulation of appropriate generic strategies is to increase product innovation to other creative crafts, focus on opening bamboo plantations and improve labor skills to attend training and development